The Sustainable Development in Papua Based on Customary Territories and Human Development Paradigm - Lefaan, Yosef; Mollet, Julius Ary; Innah, Herbert (International Journal of Social and Administrative Sciences, 2021)
The National Development Planning Agency of Indonesia has adopted the concept of development based on customary territories in Papua in the 2015-2019 National Midterm Development Plan (RPJMN). This RPJMN aimed to accommodate the mandate of the Special Autonomy Law Number 21 of 2001 regarding Special Autonomy for Papua Province. However, the RPJMN used a top-down development approach that accommodates more national and international interests than local and customary territories’ interests. The main objective of this paper is to propose a new concept of sustainable development that uses a bottom-up development approach to reconcile both interests above. The concept is supplemented with the road map and simulation to explore the progress of sustainable development. The modeling and simulation of sustainable development progress consist of the human development index (HDI), human development indicators, and electricity demand using the system dynamics model. In 2050, the lowest HDI is 63.87 in Mappi Regency. Life expectancy is 68.53 years; the schooling expecting years is 12.19 years; the schooling mean years is 6.60 years, and the expenditure per capita is Rp7,599,010, - In 2050, the highest HDI is 94.83 in Sorong Municipality. Life expectancy is 80.73 years; the schooling expecting years is 18.00 years; the schooling mean years is 15.00 years, and the expenditure per capita is Rp19,869,057 – In 2050, the electricity demand in Mappi Regency is 46,032 MWh. Meanwhile, the electricity demand in Sorong Municipality is 1,137,746 MWh.